5.1: Invited Paper: LCD or OLED: Who Wins?. Issue 1 (1st July 2013) - Barnes, David
Abstract: Historical trends point towards a future of increasing technical performance and decreasing financial performance for LCD producers. This raises questions about the motivations and abilities of producers to create an OLED infrastructure. This paper evaluates the implications through microeconomics and game theorems.